Implementasi SEMA No. 3 Tahun 2023 Dalam Mempersulit Alasan Perceraian 'Perselisihan dan Pertengkaran yang Terus Menerus' Di Provinsi Banten. - Muhammad Fajri Atqiya; Fitria Agustin (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze the implementation of Supreme Court Circular Letter (SEMA) Number 3 of 2023 as an instrument to strengthen the principle of complicating divorce, especially in cases with the reason of